2011
DOI: 10.1093/jxb/err052
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidization mechanisms: temperature environment can induce diploid gamete formation in Rosa sp.

Abstract: Polyploidy is an important evolutionary phenomenon but the mechanisms by which polyploidy arises still remain underexplored. There may be an environmental component to polyploidization. This study aimed to clarify how temperature may promote diploid gamete formation considered an essential element for sexual polyploidization. First of all, a detailed cytological analysis of microsporogenesis and microgametogenesis was performed to target precisely the key developmental stages which are the most sensitive to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 81 publications
4
123
1
Order By: Relevance
“…Lokker et al (2004) exposed four complete sterile lily genotypes to heat shock treatments and observed that three of the four genotypes became fertile by the production of viable 2n gametes. Also Pécrix et al (2011) observed a production of 2n gametes up to 24.5% in Rosa spp. through an exposition of a high temperature gradient, but the range of efficient temperatures is narrow and should be applied during early meiosis.…”
Section: Induction Of 2n Gametesmentioning
confidence: 84%
See 1 more Smart Citation
“…Lokker et al (2004) exposed four complete sterile lily genotypes to heat shock treatments and observed that three of the four genotypes became fertile by the production of viable 2n gametes. Also Pécrix et al (2011) observed a production of 2n gametes up to 24.5% in Rosa spp. through an exposition of a high temperature gradient, but the range of efficient temperatures is narrow and should be applied during early meiosis.…”
Section: Induction Of 2n Gametesmentioning
confidence: 84%
“…Moreover, frequencies may vary in different populations, within a certain genotype and during time (season) due to environmental fluctuations (Bani-Aameur et al, 1992;Crespel et al, 2006;McCoy, 1982;Ortiz et al, 1998;Ortiz & Vulsteke, 1995;Parrott & Smith, 1984;Pécrix et al, 2011;Veilleux et al, 1982). In Table 2, some recently published data on 2n gamete frequency in different (hybrid and non hybrid) populations are given.…”
Section: Practical Use Of 2n Gametes In Plant Breedingmentioning
confidence: 99%
“…For example, in rose (Rosa spp.) short periods of heat stress result in partial restitution of male meiosis and the formation of unreduced dyads, but also triads and polyads (Pecrix et al, 2011). Analysis of the effect of redox status on germline specification in maize revealed another link to abiotic stress.…”
Section: The Acquisition and Restriction Of Reproductive Fatementioning
confidence: 99%
“…Similarly, in rose (Rosa spp. ), short periods of high temperature (48 h at 30°C-36°C) can induce cytomixis and parallel and tripolar spindles at male metaphase II, generating dyads and triads at the end of male sporogenesis (Pécrix et al, 2011). Low-temperature environments can also stimulate 2n gamete formation.…”
mentioning
confidence: 99%